Effect of Different Seed Solutions on the Morphology and Electrooptical Properties of ZnO Nanorods. (4th October 2012) - Kashif, M.; Hashim, U.; Ali, M. E.; Ali, Syed M. Usman; Rusop, M.; Ibupoto, Z. H.; Willander, Magnus
Abstract : The morphology and electrooptical properties of ZnO nanorods synthesized on monoethanolamine-based seed layer and KOH-based seed layer were compared. The seed solutions were prepared in monoethanolamine in 2-methoxyethanol and potassium hydroxide in methanol, respectively. Zinc acetate dihydrate was as a common precursor in both solutions. The nanorod-ZnOs were synthesized via the spin coating of two different seed solutions on silicon substrates followed by their hydrothermal growth. The scanning electron microscopy (SEM), X-ray diffraction (XRD), photoluminescence (PL), and Raman studies revealed that the ZnO nanorods obtained from monoethanolamine-based seed layer had fewer defects, better crystals, and better alignment than those realized via KOH-based seed layer. However, the current-voltage (I-V) characteristics demonstrated better conductivity of the ZnO nanorods obtained via KOH-based seed layer. The current measured in forward bias was 4 mA and 40 μ A for ZnO-nanorods grown on KOH-based seed layer and monoethanolamine-based with the turn on voltage of approximately 1.5 V and 2.5 V, respectively, showing the feasibility of using both structures in optoelectric devices.